Kontribusi Dukungan Sosial terhadap Subjective Well-Being pada Remaja dari Keluarga Etnis Minang - Pramisya, Rizki; Hermaleni, Tesi (Universitas Brawijaya, 2021)
Subjective well-being is a lynchpin for people’s quality of life, but cultural factors may determine its dynamics. We conducted the present work within the cultural context of Minang people in West Sumatera, aimed as an empirical test on the role of social support in explaining subjective well-being among members of the ethnic group. We recruited 323 Minang adolescents aged between 15 and 19 years in West Sumatera. We found as hypothesised that social support positively and significantly explained subjective well-being wherein more social support was related to more subjective well-being (r = .51, p < .001). Previous research zoomed in on the positive relationship between social support and subjective well-being particularly within the context of individualistic culture. What has been found in our work hence may serve as an alternative to the existing research in which we observed that even within the context of the collective culture of Minang people in West Sumatera, social support positively contributed to subjective well-being.Kesejahteraan hidup menentukan kualitas hidup individu, tetapi dinamikanya mungkin dipengaruhi oleh faktor kebudayaan. Penelitian ini dilakukan dalam konteks budaya etnis Minang di Sumatera Barat dengan tujuan menguji peran dukungan sosial dalam menjelaskan kesejahteraan subjektif. Partisipan dalam penelitian ini terdiri dari 323 remaja berusia antara 15 sampai 19 tahun di Sumatera Barat, yang direkrut atas dasar purposive sampling. Sesuai dengan hipotesis yang diajukan, hasil penelitian menunjukkan bahwa dukungan sosial berperan signifikan dalam menjelaskan kesejahteraan hidup dimana semakin tinggi dukungan sosial maka semakin tinggi kesejahteraan hidup (r= .51, p < .001). Riset-riset sebelumnya menekankan bahwa hubungan positif antara dukungan sosial dan kesejahteraan hidup lebih umum ditemukan dalam budaya individualistik. Menjadi alternatif riset-riset sebelumnya, hasil penelitian ini mengimpilikasikan bahwa dalam budaya kolektif etnis Minang di Sumatera Barat, dukungan sosial berkontribusi positif dalam meningkatkan kesejahteraan hidup.